Preparation and Structure Characterization of High-Value Laminaria digitata Oligosaccharides - Cheong, Kit-Leong; Li, Jia-Kang; Zhong, Saiyi (Frontiers in Nutrition, 2022)
Algae-derived marine oligosaccharides have been reported to be promising bioactive compounds because of their various properties with health benefits and potential significance in numerous applications in industrial biotechnology. In this study, laminaran oligosaccharides (LOs) with varying degrees of polymerization were obtained through partial acid hydrolysis of laminaran derived from Laminaria digitata. Based on response surface methodology, the optimum LOs yield was obtained for acid hydrolysis laminaran at a hydrolysis time of 55 min, temperature of 71 °C, and acid concentration of 1.00 mol/L. The size-exclusion resin Bio-Gel P-2 was considered to be a better option for LOs purification. The structure of the purified oligosaccharides was analyzed through mass spectrometry and nuclear magnetic resonance. They demonstrated the main oligosaccharide structure corresponding to the connection of glucose with β-D-Glcp-(1→3)-β-D-Glcp, which was identified as laminaribiose (DP2), laminaritriose (DP3), laminaritetrose (DP4), and laminaripentaose (DP5). LOs demonstrate excellent antioxidant activities, as evidenced from their reactions with oxidizing free radicals, 1,1-diphenyl-2-picryl-hydrazyl, and 2,2'-azino-bis(3-etilbenzotiazoline-6-sulfonic acid) radicals. LOs exhibited a prebiotic effect on the growth of Bifidobacterium adolescentis and Lactobacillus plantarum. Therefore, we propose the development of LOs as natural antioxidants and prebiotics in the functional food and pharmaceutical industries.